Come in uno specchio: Il confine simbolico di Pavel Florenskij - Revello, Roberto (Scenari, 2021)
The work of Pavel Florensky clearly shows that there are relevant theoretical and moral aspects developed from issues of religious traditions. Their interest doesn’t consist solely of their historical influence, but also of their capacity to activate fresh thinking. This article especially refers to Florensky’s remarks about the symbol involving a conception of the being which isn’t “object oriented” and identity-marking, and it can be compared to this “docetistic” inspiration Henry Corbin talks about.